An institutional analysis of biofuel policies and their social implications lessons from Brazil, India and Indonesia - Mairon Bastos Lima (United Nations Research Institute for Social Development (UNRISD), 2012)
Biofuels production has quickly expanded worldwide as part of strategies to make energy economies 'greener'. Climate change mitigation and energy security have been frequent rationales behind biofuel policies, but developing countries have also emphasized the social dimensions of this new sector, flagging the inclusion of smallholder farmers in fuel production chains and the potential for poverty alleviation and rural development. However, most studies on biofuels remain focused only on the economic and ecological aspects of biofuel production and utilization, often leaving social and equity dimensions overlooked or understudied-and claims of 'pro-poor' development largely unchecked. This paper therefore sets out to examine how different developing countries have attempted to promote rural development through biofuel production, what social outcomes those strategies have created, and what lessons can be learned, such as in terms of biofuel policy design. This is done through a comparative analysis of the contexts of Brazil, India and Indonesia; three countries with important agricultural sectors that have put large-scale biofuel programmes in place. Brazil has built its biofuels policy primarily on a well-established sugarcane-ethanol industry and on an emerging biodiesel sector. As a way to stimulate those sectors, the government has put in place regulatory and economic incentives such as tax breaks, cheap credit through public banks and blending mandates Blending mandates consist of policies that determine an obligatory mixing of a certain percentage of biofuels in liquid fossil fuels commercialized (ethanol in gasoline and biodiesel in mineral diesel). to secure captive markets. In the case of sugarcane-ethanol, despite its success from an economic and an emissions reduction perspective, its social implications are grim. A highly concentrated ownership pattern and an imbalanced allocation of burdens and benefits mean that the sugarcane agribusiness captures all value-addition while the rural poor participate only as seasonal migrants working under harsh and insecure conditions...
Keywords: 330